2008
DOI: 10.1001/archpsyc.65.6.683
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Successful Smoking Cessation

Abstract: These results support polygenic genetics for success in abstaining from smoking, overlap with genetics of substance dependence and memory, and nominate gene variants for selective influences on therapeutic responses to bupropion vs NRT. Molecular genetics should help match the types and/or intensity of antismoking treatments with the smokers most likely to benefit from them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(113 citation statements)
references
References 66 publications
5
103
0
2
Order By: Relevance
“…Kaprio, Koskenvuo, & Sarna, 1981; Madden et al, 1999; Medlund, Cederlof, Floderus-Myrhed, Friberg, & Sorensen, 1976; True et al, 1997). Moreover, several genetic polymorphisms have also been found to impact therapeutic effectiveness for nicotine use disorders (Colilla et al, 2005; Johnstone et al, 2007; Uhl et al, 2008). Genetic screening may identify individuals who will best respond to naltrexone for the reduction of problem drinking (Anton et al, 2008; Oslin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Kaprio, Koskenvuo, & Sarna, 1981; Madden et al, 1999; Medlund, Cederlof, Floderus-Myrhed, Friberg, & Sorensen, 1976; True et al, 1997). Moreover, several genetic polymorphisms have also been found to impact therapeutic effectiveness for nicotine use disorders (Colilla et al, 2005; Johnstone et al, 2007; Uhl et al, 2008). Genetic screening may identify individuals who will best respond to naltrexone for the reduction of problem drinking (Anton et al, 2008; Oslin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In none of the GWAS [57,58,59,60] a significant association was found (level of significance in GWAS is α = 5 × 10 -8 ). Also in 3 (non-GWAS) studies that included many different SNPs, no significant result was found after correction for multiple testing [61,62,63].…”
Section: Resultsmentioning
confidence: 99%
“…Association was detected between dialysis survival and polymorphisms in and near genes thought to predict successful smoking cessation: PDZRN3, PTPRM , neuregulin 1 (NRG1) , SH3-domain binding protein 4 (SH3BP4) , kelch-like 29 (KLHL29) , DEAH (Asp-Glu-Ala-His) box polypeptide 35 (DHX35) , ATP-binding cassette sub-family A member 4 (ABCA4), ephrins receptor A7 (EPHA7) , proprotein convertase subtilisin/kexin type 2 (PCSK2) , tet oncogene family member 3 (TET3) , G patch domain-containing 2 (GPATCH2) , estrogen-related receptor gamma (ESRRG) , Rap guanine nucleotide exchange factor 5 (RAPGEF5) , and Ras and Rab interactor 3 (RIN3) [20,21]. Unfortunately, our dataset lacks information pertaining to smoking history.…”
Section: Discussionmentioning
confidence: 99%